NEUROTOXICITY EFFECT IN CANCER REGIMENT CARBOPLATIN-PACLITAXEL - MEITASARI, ANNISA DIYAN; SUTRISNA, EM; CHOLISOH, ZAKKY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Side effects due to chemotherapy were frequently reported and some of them require immediate treatment. Cervical cancer, breast cancer, and ovarian cancer are types of cancer that are often found in Dr. Moewardi Surakarta Hospital and 45% of the three types of cancer used the chemotherapy regimen of carboplatin-paclitaxel. Carboplatin-paclitaxel was chosen because it is a regimen that has fewer side effects. Methods: This study aims to identify the type of adverse drug reactions (ADRs) neurotoxicity, percentage, and severity, as well as to determine the risk factors for the occurrence of ADRs such as age, gender, type of cancer, number of cycles, length of stay, and types of comorbidities in cancer patients using carboplatin-paclitaxel therapy regimen in RSUD Dr. Moewardi Surakarta for the period September to December 2019. This study was an observational study with a cross-sectional design through prospective data searches. The inclusion criteria in this study were adult cancer patients on carboplatin-paclitaxel therapy who were willing to be research subjects. Results: The incidences of ADRs in patients using the carboplatin-paclitaxel therapy regimen in this study were sensory peripheral neuropathy (77.69%); motor peripheral neuropathy (3.31%); joint pain (53.72%); and muscle weakness (37.19%) The instrument to measure the severity in this study used common terminology criteria for adverse events with the results of ADRs with grade 1 (35.08%), grade 2 (61.02), grade 3 (2.88%), and at grades 4 and 5 (0%). Risk factors for gender, age, length of stay, type of cancer, number of cycles, and comorbidities did not affect the incidence of neurotoxicity in cancer patients with the carboplatin-paclitaxel therapy regimen.